Comparative Study of the Performance of Two Treatment Planning Systems Using Tests from the MPPG 5b Guidelines, TECDOC 1583 and Venselaar's Confidence Limits - Carlos Vega D'Espaux; Federico Lorenzo; Franco La Paz Mastandrea; Nicolás Larragueta (Brazilian Journal of Radiation Sciences)
This work presents a comprehensive comparative study of the performance of two Treatment Planning Systems (TPS) in radiotherapy: the Eclipse™ TPS by Varian Medical Systems, which utilizes the Analytical Anisotropic Algorithm (AAA), and the MIRS TPS by Nuclemed, which uses the Convolution and Superposition (CS) Algorithm. The evaluation of both systems was conducted following different methods, including point measurements, dose profiles, and measurements on phantoms with heterogeneities. The methodologies recommended by Venselaar, the MPPG 5b protocol by the American Association of Physicists in Medicine (AAPM), and the guidelines of the IAEA TECDOC 1583 for heterogeneity assessment were adopted for this purpose.The results indicated that the Eclipse™ system showed better overall performance in water measurements, with lower variability and greater compliance with gamma criteria (average above 95% in 3%, 2 mm profile tests). For the heterogeneity tests, Eclipse showed weakness in lung measurements, while MIRS encountered difficulty in bone calculations for our beam model and under the evaluation conditions of TECDOC 1583.